When Strategy Meets Profit: The Role of Marketing Accounting in Driving Economic Growth in the Digital Age - Deswita Deswita; Lubban Anwari Alhamidi (Dhana, 2025)
This study explores the integration of marketing and accounting functions in digital-based enterprises and how such integration influences strategic financial decision-making. Using a qualitative case study approach, data were collected from two fast-growing startups in Indonesia through in-depth interviews, internal documentation, and limited observation. The analysis focused on cross-functional collaboration and performance indicators such as Customer Acquisition Cost (CAC), Return on Marketing Investment (ROMI), and campaign budgeting accuracy. The findings reveal that marketing-accounting integration results in reduced CAC (by up to 40%), improved ROMI (from 1.4:1 to 2.6:1), and greater alignment between budget allocation and customer value creation. Marketing teams benefit from real-time financial insights, while finance departments gain better forecasting accuracy and visibility over campaign efficiency. This integration fosters transparency, shared accountability, and data-driven agility. Beyond practical improvements, the study contributes to the theoretical discourse by reinforcing the notion that marketing accounting serves as a strategic framework not merely a technical coordination within the digital economy. The findings support and extend the literature on marketing accountability and value-based management, emphasizing that digital tools enable dynamic feedback loops between market activities and financial outcomes. This study confirms the relevance of marketing-accounting integration as a conceptual model for organizational alignment, performance clarity, and value creation in digitally driven environments.